Mortality and heavy metals environmental exposure: a study in dogs - Giugliano, Roberta; Crescio, Maria Ines; Cosma, Valeria; Ciccotelli, Valentina; Vivaldi, Barbara; Razzuoli, Elisabetta (Frontiers in Veterinary Science, 2024)
Introduction Dogs are human companions and share environmental conditions with their owners. Epidemiological studies have shown that dogs seem to be good sentinel animals for the association of diseases and/or mortality provoked by chronic exposure to heavy metals (Cd, Pb). Methods In the present work, we analyze the registered death cases and population from the National Canine Registry from 2020 to 2022, involving a dog population of 582,564 and 17,507 deaths. The mortality rate in male and not-purebred dogs is higher than in female and purebred dogs, respectively. The mortality cases were cross-referenced with the environmental pollution data relating to the concentration of Cd and Pb detected, between 2012 and 2022, in the various municipalities of the Liguria region. We then calculated SMR (Standardized Mortality Rate) throughout the region and found that mortality increases from the eastern to the western Ligurian coast. Results and discussion We observed that the most polluted areas present the highest SMRs (IRR = 1.36, 95%CI: from 1.31 to 1.41). Considering dog ages, we found that mortality in young dogs is not affected by pollution, while mortality in old dogs (10–20 years old) is heavily affected by it (IRR = 8.97, 95%CI from 8.09 to 9.93). In conclusion, the data suggest the importance of canine health and biomonitor studies and provide a basis for future research involving both animal and human health.